Chronic Intermittent Hypoxia Induces Robust Astrogliosis in an Alzheimer's Disease-Relevant Mouse Model. (1st February 2019) - Macheda, Teresa; Roberts, Kelly; Lyons, Danielle N.; Higgins, Emma; Ritter, Kyle J.; Lin, Ai-ling; Alilain, Warren J.; Bachstetter, Adam D.
Highlights: Aged APP/PS1 KI mice have increased sensitive to chronic intermittent hypoxia (IH). Chronic IH increased multiple markers of astrogliosis in APP/PS1 KI mice. Chronic IH did not affect amyloid-beta levels or plaque load. Abstract: Sleep disturbances are a common early symptom of neurodegenerative diseases, including Alzheimer's disease (AD) and other age-related dementias, and emerging evidence suggests that poor sleep may be an important contributor to development of amyloid pathology. Of the causes of sleep disturbances, it is estimated that 10−20% of adults in the United States have sleep-disordered breathing (SDB) disorder, with obstructive sleep apnea accounting for the majority of the SBD cases. The clinical and epidemiological data clearly support a link between sleep apnea and AD; yet, almost no experimental research is available exploring the mechanisms associated with this correlative link. Therefore, we exposed an AD-relevant mouse model (APP/PS1 KI) to chronic intermittent hypoxia (IH) (an experimental model of sleep apnea) to begin to describe one of the potential mechanisms by which SDB could increase the risk of dementia. Previous studies have found that astrogliosis is a contributor to neuropathology in models of chronic IH and AD; therefore, we hypothesized that a reactive astrocyte response might be a contributing mechanism in the neuroinflammation associated with sleep apnea. To test this hypothesis, 10–11-month-old wild-type (WT) and APP/PS1 KI mice were exposed to 10 hours of IH, daily for four weeks. At the end of four weeks brains were analyzed from amyloid burden and astrogliosis. No effect was found for chronic IH exposure on amyloid-beta levels or plaque load in the APP/PS1 KI mice. A significant increase in GFAP staining was found in the APP/PS1 KI mice following chronic IH exposure, but not in the WT mice. Profiling of genes associated with different phenotypes of astrocyte activation identified GFAP, CXCL10, and Ggta1 as significant responses activated in the APP/PS1 KI mice exposed to chronic IH.